Three-particle correlation function in the electron-plasmon model - Vavrukh, M.V.; Slobodyan, S.B.; Tyshko, N.L. (Condensed Matter Physics, 2005)
The method of calculating the n-particle electron correlation functions for the electron-plasmon model is demonstrated. We have proposed this model earlier for the description of the strongly non-ideal electron liquid. The three-particle dynamic correlation function is calculated and presented in the elementary functions. The differences from the similar correlation function of the ordinary reference system approach in the electron liquid theory are investigated. Наведено спосіб розрахунку n-частинкових електронних кореляційних функцій електрон-плазмонної моделі, яка була запропонована авторами раніше для опису сильно неідеальної електронної рідини. Розраховано і представлено в елементарних функціях тричастинкову динамічну кореляційну функцію. Досліджено її відмінності від аналогічної кореляційної функції звичайного базисного підходу у теорії електронної рідини.